SENP1 Enhances Androgen Receptor-Dependent Transcription through Desumoylation of Histone Deacetylase 1 - Cheng, Jinke (American Society for Microbiology, 2004)
SUMO (also called Sentrin) is a ubiquitin-like protein that plays an important role in regulating protein function and localization. It is known that several nuclear receptors are modified by SUMO; however, the effect of desumoylation in regulating nuclear receptor function has not been elucidated. Here we show that androgen receptor (AR)-mediated transcription is markedly enhanced by SENP1, a member of SUMO-specific protease family. SENP1's ability to enhance AR-dependent transcription is not mediated through desumoylation of AR, but rather through its ability to deconjugate histone deacetylase 1 (HDAC1), thereby reducing its deacetylase activity. HDAC1's repressive effect on AR-dependent transcription could be reversed by SENP1 and by deletion of its sumoylation sites. RNA interference depletion of endogenous HDAC1 also reduced SENP1's effect. Thus, SENP1 could regulate AR-dependent transcription through desumoylation of HDAC1. These studies provide insights on the potential role of desumoylation in the regulation of nuclear receptor activity.